+0  
 
0
100
1
avatar

HELP PLS

 

If f(x) = x-2/x+3   and g(x) = x -4   find g(f(x)) and f(g(x)) 

 

:((((( so hard

thank you in advance

 Jun 9, 2021
 #1
avatar+121048 
+1

g(f(x))  just  means  that  we are putting   "f"  into each  "x"  in  g   and evaluating

 

So......

 

  ( (x-2)  / ( x + 3) ) -  4  =

 

(x - 2)  - 4(x + 3)

_____________   =

      x + 3

 

-3x  - 14

_______

   x + 3

 

 

 

f(g(x))  (as you may  have guessed)  means  "g"  into "'f

 

So....

 

 

(x- 4)  - 2

_________   =

(x - 4) + 3

 

x - 6

_____

 x - 1

 

 

cool cool cool

 Jun 9, 2021

36 Online Users

avatar
avatar